Chronological Evaluation of Gait Ability and Posture Balance after Adult Spinal Deformity Surgery - Tomoyoshi Sakaguchi; Masato Tanaka; Hardik Suthar; Yoshihiro Fujiwara; Koji Uotani; Shinya Arataki; Taro Yamauchi; Atsushi Sugyo; Kazuhiko Takamatsu; Yosuke Yasuda; Masami Nakagawa; Nana Takahashi (Applied Sciences, 2022)
Adult spinal deformity (ASD) is highly prevalent in persons older than 65 years, affecting more than 30% of the total population. There are many important reports that describe excellent postoperative results for ASD surgery. However, there is no report that describes a chronological evaluation of gait ability and spinal balance after ASD surgery. The present prospective study aimed to determine the recovery time of gait and spinal balance ability after adult spinal deformity (ASD) surgery. Patients with ASD (n = 25: mean age, 73.0 years) who underwent corrective surgery and preoperative and postoperative gait and spinal balance ability evaluation. Spinal radiographs and gait analysis data (static balance; single-leg standing, dynamic balance; time-up and go test, gait ability; 10 m walk velocity) were acquired preoperatively, 1 month, 6 months, and 12 months after surgery. The radiographic parameters of the spine and pelvis (lumbar lordosis; LL, pelvic tilt; PT, sagittal vertical axis; SVA, pelvic incidence; PI) were measured. The mean postoperative SVA, LL, PT, and PI-LL became 30.0 mm, 50.1 degrees, 14.1 degrees, and 0.35 degrees, respectively. Preoperatively, all spinal balance and gait ability were worse than the normal threshold (one-leg standing; 14.2 s vs. 15.0 s, time-up and go test; 13.9 s vs. 13.5 s, 10-m walk speed; 0.91 m/s vs. 1.00 m/s). At 12 months after surgery, all spinal balance and gait ability became normal or improved (single-leg standing; 14.7 s, time-up and go test; 11.0 s, 10-m walk speed; 1.09 m/s). The ODI at one-year follow-up improved from 46.8 ± 12.6% to 27.8 ± 18.1%. In conclusion, gait and spinal balance analysis revealed that ASD patients could not recover gait and spinal balance ability one month after surgery. At 12 months after surgery, gait ability and dynamic spinal balance became better than preoperative levels. However, the static spinal balance was at the same level as that of preoperative status.